ChemInform Abstract: Sulfoxide‐Directed Enantioselective Synthesis of Functionalized Tetrahydropyridines. Issue 10 (11th March 2014) - Fernandez de la Pradilla, Roberto; Simal, Carmen; Bates, Robert H.; Viso, Alma; Infantes, Lourdes
Abstract The highly selective base‐promoted cyclization of enantiopure sulfinyl dienamines provides stereodefined sulfinyl tetrahydropyridines (diastereoselectivity up to 98%).